Evaluation of lumbar angles and their clinical correlates in a Nigerian population - Onyemaechi, Ndubuisi O. C. (International Journal of Research in Medical Sciences, 2017)
Background: There is paucity of data on the geometric angles of the lumbosacral spine in Nigeria and other African countries. The objective was to study the lumbar angles in our population and causes of variations if any. Methods: The lateral views of the lumbosacral spine radiographs of 300 Nigerian subjects were studied. The lumbar angles measured were lumbosacral angle (LSA), Lumbar lordosis angle (LLA), Sacral inclination angle (SIA) and lumbosacral disc angle (LSDA). The demographics and anthropometric measurements of the subjects such as weight, height, body mass index (BMI), hip circumference (HC), waist circumference (WC) and waist-hip ratio (WHR) were also recorded. Results: The mean values of the angles were as follows: LSA=37.80±9.20; LLA=40.40±11.20; SIA=38.70±8.90 and LSDA=14.60±3.40. There was a positive correlation between the weight, BMI, HC and WC of the subjects and LSA. A significant association was noted between the height, weight, BMI, HC, WC and WHR of the subjects and LLA. Whereas SIA was significantly affected by sex, weight, BMI, HC and WC of the subjects, LSDA was determined by age, BMI, WC and WHR. Conclusion: The mean values of these angles may form the reference values for the Nigerian population. Overweight and obesity were associated with increased lumbar angles.